Agnes Heller: indivíduo e ontologia social - fundamentos para a consciência ética e política do ser social - Veroneze, Renato Tadeu (2013)
This research intends to investigate the contributions of Agnes Heller s thoughts, which was formulated between 1956 and 1978, to the construction of the social been ethical and political consciences. Agnes Heller, a name with an international projection in the Contemporary Philosophy, was a Georgy Lukács pupil and assistant, who was the greatest marxism exponent, mostly in the Esthetics and the Ontology of the Social Being areas. She was considered by Lukács the more productive member of group called School of Budapest . The objective of this group was to creat a line of thought based on Lukács s theoretical and philosophical writings, re-read Marxian work to heve a correct understanding in Marx s method. She remained in Hungary until 1978 and produced some works in which we see expressed the Budapest school s kind of guidance. The ideo-political persecution in Hungary, Heller did that come out of his native in 1978, to reside in Australia with Ferenc Fehér. In 1986 she was bound to Hannah Arendt s post of Political Science and Philosophy at the New School for Social Research, in New York, and she is until now in fruitful activities in the United States of America and Hungary. Her works written until 1978, therefore, during the Marxist time, bring important contributions to consolidate the ethical and political conscience of the social being, having for basis the ontology of the social being, its theory about everyday life and its writings direct to the ethical and political conscience. We believe Heller tried to complete the big project of Lukács of writing an Ethics in the Marxist s point of view, so we set from the hypothesis that her theory points towards a praxis philosophy and non-alienated everyday life experiences. We seek to understand the main fundaments of her theory as a proposal for a way of thinking, being and conscientious acting at and to everyday life, in the social s relations and inter-relation, in ethical and political s proposition of the social life, towards the collective and individual revolutionary subject. Therefore, our research objective is the recognition of individuality while the sine qua non condition for ethical and political conscience of the social being